MAIN DIRECTIONS FOR ENSURING ECONOMIC SECURITY OF ЕNTERPRISES DURING THE WAR - Alistratenko, Mykyta (Social Development: Economic and Legal Issues, 2026)
The dynamics of the world economic system are undergoing rapid transformations, primarily due to outbreaks of local armed conflicts. In these realities, the study of trends in Ukraine’s economic security is impossible without a deep analysis of the challenges and threats that are formed in the external environment. In view of this, the article carries out a comprehensive analysis of the security situation of domestic enterprises in wartime. The work reveals the essential characteristics of ensuring economic security and explores the nature and destructive impact of economic offenses. It is noted that ensuring economic security during wartime is a fundamental condition for the survival of the state, since modern war is not only a confrontation of armies, but also a war of resources and economic systems for endurance. It is found that during martial law, classical market mechanisms undergo deformation, so state policy is reoriented to a strict anti-crisis management and mobilization model. It is determined that today in the scientific community, there is no single approach to defining the essence of economic security, and the concept itself is interpreted quite diversely. In particular, the security of entrepreneurial activity is considered in a wide range: from “protection from selfish crimes” and “minimization of internal and external threats” to “maximum effective management of corporate resources”. It is substantiated that ensuring the economic security of an enterprise during a war requires a radical restructuring of management approaches with a focus on survival and maintaining the viability of the business. The first and most important direction in this is financial security and the accumulation of liquidity, since in crisis conditions, the availability of liquid money determines the company’s ability to continue functioning. It is proven that in general, the entire system of economic security during a war moves from long-term planning to flexible scenario management, where the main criterion for effectiveness becomes the ability of the system to quickly recover after external shocks.